2001
DOI: 10.1016/s0014-5793(01)02085-3
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus infection increases the expression and activity of ecto‐ATPase (CD39) and ecto‐5′nucleotidase (CD73) on endothelial cells

Abstract: We describe enhanced expression and enzymatic activity of ecto-ATPase and ecto-5P Pnucleotidase on CMV infected endothelial cells as compared to uninfected cells. These ectoenzymes play a major role in modulation of platelet activation and aggregation. Furthermore, adenosine has a modulatory effect upon inflammation. Addition of ATP, ADP or AMP to cultures of CMV infected or uninfected endothelial cells revealed increased turnover of AMP in CMV infected endothelial cells. In addition, the superoxide production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 29 publications
(36 reference statements)
2
26
0
1
Order By: Relevance
“…Levels of antioxidants enzymes in platelets of different study groups: SOD and CAT activities in the platelets of type 2 DM subjects and control group (data are expressed as mean ± SEM).There were no significant differences, as determined by Student's t-test. A B interest, the metabolism of extracellular nucleotides plays an important regulatory role in the control of adequate hemostasis, mainly by regulating platelet coagulant status [61]. In the present study, we observed an increase of 5'NT activity in diabetic platelets (Fig.…”
Section: Discussionsupporting
confidence: 63%
“…Levels of antioxidants enzymes in platelets of different study groups: SOD and CAT activities in the platelets of type 2 DM subjects and control group (data are expressed as mean ± SEM).There were no significant differences, as determined by Student's t-test. A B interest, the metabolism of extracellular nucleotides plays an important regulatory role in the control of adequate hemostasis, mainly by regulating platelet coagulant status [61]. In the present study, we observed an increase of 5'NT activity in diabetic platelets (Fig.…”
Section: Discussionsupporting
confidence: 63%
“…Previously, we observed that infection of human endothelial cells in vitro with CMV leads to increased activity of ectoenzymes, such as ecto-nucleotide triphosphate diphosphohydrolase (ENTPD)-1, also known as ectoapyrase or CD39, and ecto-5Јnucleotidase (CD73) (6). It has been shown that ENTPD1 is a protective factor in vascular injury, including reperfusion injury models and transplant rejection (7)(8)(9).…”
mentioning
confidence: 99%
“…It has been shown that ENTPD1 is a protective factor in vascular injury, including reperfusion injury models and transplant rejection (7)(8)(9). Thus, this ecto-enzyme is able to hydrolyze adenosine triphosphate (ATP) through adenosine diphosphate (ADP) to adenosine monophosphate (AMP), whereas AMP can be hydrolyzed to adenosine by CD73 (6). Local extracellular ATP and ADP show proinflammatory and proaggregatory properties, respectively (10,11).…”
mentioning
confidence: 99%
“…Kas-Deelen et al [70] reported that cytomegalovirus infection induced increased expression and activity of ecto-NTPDase (CD39) and ecto-5'-nucleotidase (CD73) in endothelial cells. In this context, the production of adenosine is probably enhanced.…”
Section: Immunomodulation and Cell-cell Interactionsmentioning
confidence: 99%